A Proposal for the Implementation of an English for Specific Purposes Specialization in a Master's Degree Program in Second Languages and Cultures with Emphasis in English as a Foreign Language - Saborío Pérez, Ileana; Valenzuela Arce, Nandayure (Revista de Lenguas Modernas, 2009)
.